2016
DOI: 10.1021/acs.jced.5b00624
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Modeling of MgCl2 Solubility in Methanol, Ethanol, 2-Propanol, and Their Mixtures from 283 to 343 K

Abstract: MgCl2-supported Ziegler–Natta catalyst plays an important role in polyolefin industry. The solubility of MgCl2 in various alcohols has been studied to understand the mechanisms involved in the preparation of the catalyst. The solubility of anhydrous MgCl2 in methanol, ethanol, and 2-propanol and their mixtures was measured by a dynamic method at temperatures from 283.2 to 343.2 K. The solubility was found to increase with increasing temperature, but the increasing rate was dependent on the composition of solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The MgCl 2 -nROH adducts were synthesized through an azeotropic distillation method (step a in Scheme 1), stirring for 3 h at 95 8C under inert atmosphere a solution of MgCl 2 in alcohol (either methanol or ethanol, 12 mL per gram of MgCl 2 ) and toluene, according to a procedure well established in the literature, [78,123] and in the same way as reported in previous works. [45,59] At the end of the process, the precipitation of the MgCl 2 -nCH 3 OH or MgCl 2 -nCH 3 CH 2 OH powders occurred, in agreement with the MgCl 2 solubility models proposed by Zeng et al [124] The controlled dealcoholation of the MgCl 2 -nROH adducts (step b) was achieved in N 2 flux (20 mL/min), heating the samples with a temperature ramp of 2 8C/min up to 250 8C, followed by 30 min of isotherm at the same temperature. The final temperature of this thermal treatment was chosen on the basis of the thermogravimetrical analysis (TGA), to assure the complete removal of all the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 alcohol molecules.…”
Section: Materials Synthesissupporting
confidence: 76%
“…The MgCl 2 -nROH adducts were synthesized through an azeotropic distillation method (step a in Scheme 1), stirring for 3 h at 95 8C under inert atmosphere a solution of MgCl 2 in alcohol (either methanol or ethanol, 12 mL per gram of MgCl 2 ) and toluene, according to a procedure well established in the literature, [78,123] and in the same way as reported in previous works. [45,59] At the end of the process, the precipitation of the MgCl 2 -nCH 3 OH or MgCl 2 -nCH 3 CH 2 OH powders occurred, in agreement with the MgCl 2 solubility models proposed by Zeng et al [124] The controlled dealcoholation of the MgCl 2 -nROH adducts (step b) was achieved in N 2 flux (20 mL/min), heating the samples with a temperature ramp of 2 8C/min up to 250 8C, followed by 30 min of isotherm at the same temperature. The final temperature of this thermal treatment was chosen on the basis of the thermogravimetrical analysis (TGA), to assure the complete removal of all the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 alcohol molecules.…”
Section: Materials Synthesissupporting
confidence: 76%
“…When it comes to electrolytes, their solvation in alcohols and aqueous alcohol solutions are of great significance in many industrial and natural processes [ 22 , 23 , 24 ]. So, the mixtures of alcohols with organic or inorganic salts have been vastly investigated, mostly focusing on understanding the physicochemical properties of the systems [ 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Of particular interest, it has been reported that the dissolution of some salts in certain alcohols in appropriate molar ratios leads to a significant drop in freezing points with respect to the composing pure components, forming the neoteric class of solvents coined as deep eutectic solvents (DESs) [ 23 , 24 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The solubilities are affected by the physical interactions between various species in the solution, and the formation of different solid phases which are dependent on the solvent concentrations and temperature. For mixed-solvent systems containing electrolytes, the computational and predictive ability of the MSE model has been verified by many studies. , The MSE framework utilizes the MSE activity model, which contains the extended Debye–Hückel term, that accounts for long-range interactions, a UNIQUAC term that accounts for short-range interactions, and a middle range that includes ionic interactions. In this study, the solubility of the MgCl 2 –NiCl 2 –H 2 O ternary system at 303, 313, and 323 K was calculated using the Mixed Solvent Electrolyte (MSE) model under the OLI software.…”
Section: Comparison and Discussionmentioning
confidence: 99%